2020
DOI: 10.3389/fsurg.2020.620034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Short-Term Outcomes Between Endovenous 1,940-nm Laser Ablation and Radiofrequency Ablation for Incompetent Saphenous Veins

Abstract: Background: Radiofrequency ablation (RFA) has shown faster recovery and lower pain scores compared to Endovenous laser ablation (EVLA) for treatment of varicose veins. However, a comparison of 1,940-nm EVLA and RFA has not been reported. This study compared short-term outcomes using 1,940-nm EVLA and RFA for varicose veins.Methods: Between April 2018 and June 2018, 43 patients (83 incompetent saphenous veins) were treated with 1,940-nm EVLA and 37 patients (64 incompetent saphenous veins) with RFA. Follow-up d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“… 23 , 24 , 43 In a randomized study involving 580 legs with GSV insufficiency, Rasmussen 43 and Lawaetz 24 found that the 5‐year occlusion rate was 25% lower in the UFGS group. These observations are consistent with several other reports on VU patients, where relapse rates in the treatment of VUs with UGFS ranged between 5% and 13% within a year, 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 whereas relapse rates of studies involving EVLA were ranging between 0% and 9%. 37 , 38 , 39 , 40 In a study by Wysong et al, 41 in which 30 patients were treated with EVLA in combination with foam sclerotherapy and/or phlebectomy of incompetent tributaries, no ulcer reoccurrence was observed within a median follow‐up time of 448 days.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 23 , 24 , 43 In a randomized study involving 580 legs with GSV insufficiency, Rasmussen 43 and Lawaetz 24 found that the 5‐year occlusion rate was 25% lower in the UFGS group. These observations are consistent with several other reports on VU patients, where relapse rates in the treatment of VUs with UGFS ranged between 5% and 13% within a year, 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 whereas relapse rates of studies involving EVLA were ranging between 0% and 9%. 37 , 38 , 39 , 40 In a study by Wysong et al, 41 in which 30 patients were treated with EVLA in combination with foam sclerotherapy and/or phlebectomy of incompetent tributaries, no ulcer reoccurrence was observed within a median follow‐up time of 448 days.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, the use of minimally invasive endovenous interventions, including endovenous laser and foam sclerotherapy, has gained increasing attention due to the lack of open surgical incisions, the possibility to be carried out under local/tumescent anaesthesia and consequently, their lower postoperative morbidity 12,18 . So far, a large series of studies has demonstrated the efficacy of thermal and non‐thermal endovenous techniques in reflux elimination in patients with axial venous reflux 19–30 . However, comparative studies on the different types of endovenous treatments in patients suffering from VUs are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment has been shifted to the less invasive techniques as radiofrequency ablation (RFA) and endovenous laser ablation (EVLA) that have been developed with better clinical outcomes, lower pain and earlier return to daily activities compared with traditional surgery [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, tumescent anesthesia, which requires many injections throughout the length of the target vein, is needed for individuals receiving EVLA treatment. Some individuals continue to feel discomfort weeks after surgery (5) .…”
Section: Introductionmentioning
confidence: 99%